Sex differences in left ventricular stroke work and cardiac power output per unit myocardium relate to blood pressure in apparently healthy adults - Jing Lu; Lixue Yin (PLoS ONE, 2023)
Background Left ventricular stroke work per unit myocardium (LVSWM) and cardiac power output per unit myocardium (CPOM) are important measures of myocardial workload. The sex differences in the myocardial workload and its correlation with blood pressure remain largely unclear. Objectives The purpose of this study is to investigate the sex differences in LVSWM and CPOM, and to relate them to blood pressure in a cohort of apparently healthy adults. Methods The LVSWM and CPOM were estimated in 596 age- and heart rate-matched apparently healthy adults (298 men) using transthoracic echocardiography combined with cuff-measured brachial blood pressure. The data were compared between sexes, and the sex differences in LVSWM and CPOM were related to blood pressure. Results After adjustment for the blood pressure, the LVSWM and CPOM were higher in women than in men [75.0 (73.7–76.4) vs 64.9 (63.5–66.2) cJ/100g for LVSWM, and 912.4 (894.1–930.6) vs 780.2 (762.0–798.5) milliwatt/100g for CPOM, respectively; all P<0.001]. After adjustment for the LVSWM and CPOM, the mean systolic and diastolic blood pressure were 7.4 mm Hg and 5.2 mm Hg higher in men than in women, respectively (all P<0.001). Conclusions For any given blood pressure, the workload per unit myocardium is higher in apparently healthy women than in their male counterparts. A sex-specific definition of normal blood pressure with a relatively lower threshold for women can minimize the sex differences in the myocardial workload, which might reduce the potentially comparatively higher risk of heart failure in women.